FEDERACIÓN CRISTIANA DE CAMPESINOS SALVADOREÑOS (FECCAS) AND UNIÓN DE TRABAJADORES DEL CAMPO (UTC): THE MAKING OF THE SALVADORAN PEASANTS MOVEMENT REVISITED - Arriola, Francisco Joel (2019)
In this paper, I review the process of making of the Federación Cristiana de Campesinos Salvadoreños (FECCAS) and the Unión de Trabajadores del Campo (UTC), the two largest peasant organizations that, during the 1970s, promoted, together with a multiplicity of popular urban actors, the radicalized cycle of unarmed mobilizations that preceded the Salvadoran Civil War (1981-1992). Although the macro-processes and the big structures that enabled the emergence of the peasant political struggle of the period and the constitution of their organizational structures are taken into account, this paper privileges an approach that helps us to account for local processes and the courses of action deployed by multiple actors in specific contexts that were at the base of the formation of FECCAS and UTC. I conclude that these two rural organizations and their distinctive characteristics resulted invariably from the interactive action of three basic actors: progressive sectors of the Catholic Church, militants of the Political Military Organizations (OPM) and peasant leaders. The specific way in which these three actors articulated themselves and the way in which their action crystallized in the formation and development of the aforementioned organizations, nevertheless, followed complex and particular paths in each specific region.